Endovascular Treatment of Ruptured Middle Cerebral Artery Aneurysms With a Low-Profile Visualized Intraluminal Support Device - Xue, Gaici; Zhou, Yu; Liu, Peng; Zuo, Qiao; Yang, Pengfei; Fang, Yibin; Li, Qiang; Zhao, Rui; Xu, Yi; Hong, Bo; Huang, Qinghai; Liu, Jianmin (Frontiers in Neurology, 2021)
Objective: Stenting in ruptured middle cerebral artery (MCA) aneurysms was reported with a high perioperative complication rate. However, the treatment devices and physician’s experience continued evolving. We performed this retrospective study to evaluate the safety and efficacy of LVIS stent-assisted coiling for ruptured MCA aneurysms. Methods: Patients with acutely ruptured MCA aneurysms treated between November 2014 and October 2019 were retrospectively reviewed. Clinical and angiographic data of those treated with LVIS stents were collected from a prospectively maintained database. Results: A total of 40 patients with 40 ruptured MCA aneurysms were enrolled, which comprised 26.3% (40/152) of all the ruptured MCA aneurysms at the same time. All stents were successfully deployed except for one (2.5%) with poor stent opening. Ischemic procedure-related complications were encountered in 3 patients (7.5%). One patient died of complications related to high-grade SAH on admission. Follow-up (mean 15.9 months) angiography was performed for 36 patients, which showed 33 (91.7%) aneurysms were completely occluded, 1 (2.8%) was improved, 1 (2.8%) was stable and 1 (2.8%) were recanalized. Clinical follow-up (mean 29.6 months) was available for all survived patients, which showed 38 (95.0%) patients had favorable neurologic outcomes (mRS score 0-2) and 2 (5.0%) patients had poor neurologic outcomes. Conclusion: The use of LVIS stents is feasible, safe and effective with glycoprotein IIb/IIIa inhibitor for the treatment of ruptured MCA aneurysms in the acute setting. Prospective, multicenter studies with larger sample sizes are still required to further evaluate the safety and long-term efficacy.